Contrasting Roles of Neural Firing Rate and Local Field Potentials in Human Memory - Ekstrom, Arne (2007)
Recording the activity of neurons is a mainstay of animal memory research, while human recordings are generally limited to the activity of large ensembles of cells. The relationship between ensemble activity and neural firing rate during declarative memory processes, however, remains unclear. We recorded neurons and local field potentials (LFPs) simultaneously from the same sites in the human hippocampus and entorhinal cortex (ERC) in patients with implanted intracranial electrodes during a virtual taxi-driver task that also included a memory retrieval component. Neurons increased their firing rate in response to specific passengers or landmarks both during navigation and retrieval. Although we did not find item specificity in the broadband LFP, both θ- and γ-band LFPs increased power to specific items on a small but significant percent of channels. These responses, however, did not correlate with item-specific neural responses. To contrast item-specific responses with process-specific responses during memory, we compared neural and LFP responses during encoding (navigation) and retrieval (associative and item-specific recognition). A subset of neurons also altered firing rates nonspecifically while subjects viewed items during encoding. Interestingly, LFPs in the hippocampus and ERC increased in power nonspecifically while subjects viewed items during retrieval, more often during associative than item-recognition. Furthermore, we found no correlation between neural firing rate and broadband, θ-band, and γ-band LFPs during process-specific responses. Our findings suggest that neuronal firing and ensemble activity can be dissociated during encoding, item-maintenance, and retrieval in the human hippocampal area, likely relating to functional properties unique to this region.